2019
DOI: 10.1002/ange.201909623
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐Mobility Spectrometry Can Assign Exact Fucosyl Positions in Glycans and Prevent Misinterpretation of Mass‐Spectrometry Data After Gas‐Phase Rearrangement

Abstract: The fucosylation of glycans leads to diverse structures and is associated with many biological and disease processes. The exact determination of fucoside positions by tandem mass spectrometry (MS/MS) is complicated because rearrangements in the gas phase lead to erroneous structural assignments. Here, we demonstrate that the combined use of ion‐mobility MS and well‐defined synthetic glycan standards can prevent misinterpretation of MS/MS spectra and incorrect structural assignments of fucosylated glycans. We s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Overall, our findings indicate that fucose is prone to migrate towards the O6 position of GlcNAc in the gas phase, regardless of its initial location. Because fucose does not migrates towards hexoses, it was suggested that it rearranges to the oxygen or nitrogen of the acetamido moiety [17] . Our findings indicate that the fucose migrates towards hydroxyl groups instead.…”
Section: Figurementioning
confidence: 64%
See 2 more Smart Citations
“…Overall, our findings indicate that fucose is prone to migrate towards the O6 position of GlcNAc in the gas phase, regardless of its initial location. Because fucose does not migrates towards hexoses, it was suggested that it rearranges to the oxygen or nitrogen of the acetamido moiety [17] . Our findings indicate that the fucose migrates towards hydroxyl groups instead.…”
Section: Figurementioning
confidence: 64%
“…To date, as a result of the proposed in‐source migration mechanism, individual fucosylated structures could not be isolated for further IR analysis. This observation was confirmed by IM‐MS [17] . In this context, structural data supporting that the structure of protonated fucosylated structures could be retained at all through MS workflows, as well as reference data supporting the structural characterization of fucosylated products were lacking.…”
Section: Figurementioning
confidence: 78%
See 1 more Smart Citation
“…Recent works by Mucha et al [16] . and Toraño et al [17] . showed that migration of fucose from one residue to another may occur as early as at the ionisation stage in a mass spectrometric workflow using IR spectroscopy and ion mobility.…”
Section: Figurementioning
confidence: 99%
“…For example, it was shown that synthetic oligosaccharide isomers can be successfully separated using TWIMS, despite only minor differences in their regio‐ and stereo‐chemistry at a singly glycosidic bond (Hofmann et al, 2015). Furthermore, it was demonstrated that fragment‐based approaches can identify fucosylated (Sastre Toraño et al, 2019) and sialylated linkages (Hofmann & Pagel, 2017; Hofmann et al, 2017; Lane et al, 2019) which can be used to determine characteristic features on milk oligosaccharides and complex N ‐glycans (Harvey et al, 2018b; Pagel & Harvey, 2013). The combination of mass measurement and IM‐MS analysis also enabled the assignment and identification of isomeric glycopeptides and separation into different charge states (Creese & Cooper, 2012; Zhu et al, 2015).…”
Section: Ion Mobility‐mass Spectrometrymentioning
confidence: 99%